Students’ Perception on Using Songs and Poems from learnenglish kids as Autonomous Learning Activity to Increase Vocabulary - Isladara, Nadhira Puti; Marlina, Leni (Universitas Negeri Padang, 2024)
The purpose of this research is to reveal EFL students’ perception regarding the efficacy of LearningEnglish Kids as a tool for autonomous learning aimed at increasing vocabulary. The perception can be negative or positive based on the experience of each student. This research uses descriptive research with a quantitative approach. This research was conducted from the researcher’s observation during teaching practice at SMP 15 Padang where certain issues were identified. Utilizing random sampling, 65 students from six classes were selected as samples. Data collection involved distributing a questionnaire comprising 40 items and conducting interviews via online, focusing on 9 questions. The analysis indicates that both songs and poems from LearnEnglish Kids serve as effective autonomous learning tools, fostering positive perception on students’ vocabulary development across reading, speaking, writing, and listening skills. Specifically, students reported improvements in their reading comprehension and fluency, as well as enhanced speaking, writing, and listening abilities, underscoring the comprehensive advantages of integrating these resources into language education.